Nutrition and Food Supplies - Standing Joint Committee of Industrial Women's Organisations (London : The Labour Party)
1936-09 1936 1930s 33 pages : illustration The Ministry of Health in 1932 published a report on Diet in Poor Law Children’s Homes, which considered the question of a properly balanced diet with a careful eye to economy. The conclusion was that in an institution for 200 children, the weekly cost per head per week, for food alone, would be about 4/6½, if all provisions were bought at contract prices. Sir John Orr, who is a recognised authority on Nutrition, has stated in his recent book “Food, Health and Income,” that a diet sufficient to maintain the fullest health can only be assured where there is an expenditure of 10/- per head per week on food. EXPENDITURE ON FOOD How do these various estimates of the cost of a minimum diet, and Sir John Orr’s estimate for the “Optimum,” compare with the actual amounts which families can spend on food. Sir John Orr argues that half the population are living below his ideal standard. There are, he says, 4½ million people who can spend no more than 4/- a week upon food. Their diet is deficient in every constituent. There are 9 millions who spend no more than 6/- per week. Their diet is adequate in fuel foods and in tissue forming foods, but deficient in protective foods. There are 9 millions who spend no more than 8/- per week. Their diet is deficient in certain protective elements. The fourth group of 9 millions who spend 10/- per week, have an almost completely adequate diet. In two higher groups of 9 millions and 4½ millions respectively — spending 12/- and 14/- per week — there is a surplus of the various constituents. 12 127/NU/5/5/1/12